Improving Heat Exchange Performance of Massive Concrete Using Annular Finned Cooling Pipes - Lemu Zhou; Fangyuan Zhou; Hanbin Ge (Advances in Materials Science and Engineering)
Cracks will be generated due to high internal temperature of the massive concrete. Postcooling method is widely employed as a standard cooling technique to decrease the temperature of the poured mass concrete. In this paper, an annular finned cooling pipe which can increase the heat transfer area between the flowing water and its surrounding concrete is proposed to enhance the cooling effect of the postcooling method. Analysis of the interior temperature variation and distribution of the concrete block cooled by the annular finned cooling pipe system and the traditional cooling pipe system was conducted through the finite element models. It is found that, for the concrete block using the proposed annular finned cooling pipe system, the peak value of the interior temperature can be further lowered. Compared with the traditional cooling pipe, the highest temperature of concrete with an annular finned cooling pipe appears earlier than that with the traditional cooling pipe.